How Democracy Functions in Ethnically Divided Societies, and Power-Sharing Minorities - Тарас Лупул (Історико-політичні проблеми сучасного світу)
Book review Licia Cianetti "The Quality of Divided Democracies. Minority Inclusion, Exclusion, and Reprsentation in the New Europe"